Zircon U–Pb ages, geochemistry, and Sr–Nd–Pb–Hf isotopes of the Mugagangri monzogranite in the southern Qiangtang of Tibet, western China: Implications for the evolution of the Bangong Co‐Nujiang Meso‐Tethyan Ocean. (10th February 2021) - Huang, Han‐Xiao; Dai, Zuo‐Wen; Liu, Hong; Li, Guang‐Ming; Huizenga, Jan Marten; Zhang, Lin‐Kui; Huang, Yong; Cao, Hua‐Wen; Fu, Jian‐Gang
Abstract : We present in‐situ zircon laser ablation‐inductively coupled plasma‐mass spectrometry (LA‐ICP‐MS) U–Pb ages, whole‐rock geochemistry, and Sr–Nd–Pb–Hf isotopes of the Mugagangri monzogranite in the southern margin of the Qiangtang Block, Tibet, western China. The zircons yield a U–Pb age of ca. 123 Ma. The hornblende‐bearing monzogranite shows metaluminous to weak peraluminous and high‐K calc‐alkaline characteristics exemplified by high silica (SiO2 = 67.57–70.57 wt%), high aluminium (Al2 O3 = 14.68–15.78 wt%), high potassium (K2 O = 4.00–5.14 wt%), high alkali (K2 O + Na2 O = 7.88–8.62 wt%), and low calcium contents (CaO = 1.72–2.17 wt%), with the aluminium saturation index (A/CNK) ranging from 0.98 to 1.09, suggesting that the Mugagangri monzogranite is a metaluminous to weak peraluminous I‐type high‐K calc‐alkaline granite. Geochemically, similar to the arc magmas, the monzogranite is enriched in large‐ion lithophile elements, and relatively depleted in high‐field‐strength elements. The monzogranite displays relatively high ( 87 Sr/ 86 Sr)i values (0.70972–0.71240), uniform εNd ( t ) values (−2.24 to −3.40), variable zircon εHf ( t ) values (−14.1 to +8.0), and high radiogenic Pb isotopic values ( 206 Pb/ 204 Pb = 18.588–18.790, 207 Pb/ 204 Pb = 15.616–15.642, and 208 Pb/ 204 Pb = 38.838–39.053). These geochemical characteristics indicate that the monzogranite was derived from a mixed source comprising ancient crustal and mantle materials, and experienced fractional crystallization during emplacement. We propose that the parental magma of the Mugagangri monzogranite was most likely generated during northward subduction of the Bangong Co‐Nujiang Meso‐Tethys Ocean. Abstract : At ca. 120 Ma, the mantle wedge partially melted due to metasomatism of subduction‐derived fluids and generated basaltic melts, which resulted in partial melting of crust and generation of felsic melts. Mantle‐derived basaltic magmas and crust‐derived felsic magmas mixed in deep‐seated magma chamber and formed mixed magmas. These mixed magmas experienced pronounced fractional crystallization in the magma chamber or during ascend, and then formed a series of medium‐acidic intrusive rocks represented by the Mugagangri monzogranite.